Development and characterization of an immunoaffinity column for the detection of danofloxacin residues in milk samples - NIU,Rui (2019)
Abstract In this study, an immunoaffinity column was prepared by covalently coupling of polyclonal antibody against danofloxacin (DAN) with chitosan microparticles and its potential application to selective extraction of DAN from food samples was also evaluated. The produced antibody exhibited high sensitivity, with an IC50 value of 4.56 ng/mL towards DAN, and good specificity, with less than 0.5% of cross-reactivity towards DAN structurally related compounds. The developed immunoaffinity column had an approximate binding capacity of 2300 ng/mL gel and a relative standard deviation (RSD) of 3.7% among columns. The immunoaffinity columns were then challenged with DAN-fortified milk samples, recoveries of DAN were found to be in the range of 83.8% to 98.8%, indicating the prepared immunoaffinity column is suitable for use as an efficient extraction method to detect DAN residues in food products.